INDICATION OF OBLIGATION AVOIDANCE BY PT. LIPPO CIKARANG TBK. TO INCREASE COMPANY PROFITS - Riyono, Kenley (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2024)
This research is intended to provide new findings in the case of the Meikarta project and the responsibility of PT Lippo Cikarang Tbk. The sample used is based on financial statements from period to period to determine the condition of the company at that time. The approach of this research is descriptive analysis to explain the condition of the target market at that time. The results of this study show that PT Lippo Cikarang Tbk. gain a significant increase in profits after avoiding its obligations to the development of the company. As well as the systematic abdication of responsibility for the Meikarta project that had been planned from the start. Finally, the Meikarta project went bankrupt and its subsidiaries became burdened by various debts. The results of this study are expected to be implemented for one’s insight into earnings management through the Meikarta case. Insight into earnings management practices must be known and careful about because they can have negative and positive impacts.